Implementasi Strategi Pelatihan dan Pengembangan Sumber Daya Manusia: Studi Kasus Deradikalisasi terhadap Mantan Napi Terorisme di Yayasan Lingkar Perdamaian Kabupaten Lamongan - Ahmad Jundulloh; Ah. Ali Arifin (Journal of Islamic Management, 2021)
The Lamongan District Peace Ring Foundation needs training and development for former terrorism convicts, so that they can escape from radical networks and become qualified human resources. This study aims to describe the training strategy and human resource development and the factors that support and obstruct it at the Lamongan District Peace Ring Foundation. Researchers used qualitative research methods with a descriptive approach. This study uses data collection techniques by means of interviews, documentation, and observation. The results of this research are the human resource training strategy applied to former terrorism convicts by the Lamongan District Peace Circle Foundation has a goal, namely to leave the old community and change lifestyles, create integrity with the community, improve skills and abilities, know how to be entrepreneurial